2015
DOI: 10.1257/aer.20131564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Behaviorally Motivated Policy: Experimental Evidence from the Lightbulb Market

Abstract: Imperfect information and inattention to energy costs are importantA fundamental assumption in traditional policy analysis is that people's choices identify their true preferences. In practice, however, many policies are at least partially predicated on the idea that consumers' choices may not maximize their own welfare. Examples include consumer financial protection, taxes and bans on drugs, alcohol, cigarettes, and unhealthy foods, and subsidies and mandates for energy-efficient products. To evaluate such po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
250
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(260 citation statements)
references
References 62 publications
10
250
0
Order By: Relevance
“…Chetty et al 2009, Tiefenbeck et al 2018. This can cause individuals to overlook differences in usage cost (Allcott and Taubinsky 2015) and excessively focus on the upfront price. It can thus lead individuals to favor energyinefficient products, even though it is not even in their own self interest, and compound problems of environmental pollution and climate change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chetty et al 2009, Tiefenbeck et al 2018. This can cause individuals to overlook differences in usage cost (Allcott and Taubinsky 2015) and excessively focus on the upfront price. It can thus lead individuals to favor energyinefficient products, even though it is not even in their own self interest, and compound problems of environmental pollution and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the potential of information to overcome salience bias, without focusing on energy labels. For instance, Allcott and Taubinsky (2015) conduct an incentive-compatible field experiment and find that information on lifetime cost increases the WTP for CFL over incandescent light bulbs. In addition, Camilleri and Larrick (2014) find that consumers purchase energy-efficient cars more often when lifetime operating cost are displayed.…”
Section: Introductionmentioning
confidence: 99%
“…Low financial incentives can inadvertently communicate to an actor that the behavior is not valuable, counteracting or "crowding out" the actor's intrinsic motivations and resulting in decreased conservation (Gneezy et al 2011). Incentives could also simply fail because the actor is unaware of the potential benefit (e.g., savings from energy-efficient light bulbs; Allcott & Taubinsky 2015) or because there is an actual or perceived inability to change the behavior (Bandura 1994) ( Figure 3).…”
Section: Barriersmentioning
confidence: 99%
“…Setting the online slider-bar to start at 100% cost-share (on a range of 0%-100%) in an online auction for conservation contracts that require farmers to adopt conservation practices resulted in higher bids than setting the slider bar initially at 0% (Messer et al 2015) (Figure 3). These type of nudges are attractive because they may be less costly and better preserve freedom of choice than regulations or price-based incentives (e.g., taxes, subsidies) (Allcott & Taubinsky 2015).…”
Section: Rationale and Evidencementioning
confidence: 99%
“…Making these calculations can be burdensome for consumers, as suggested by the results presented in Allcott and Taubinsky (2015). Participants of an online randomized control trial in the US could choose between light bulbs with different levels of energy efficiency.…”
Section: Energy and Investment Literacymentioning
confidence: 99%